2023
DOI: 10.1590/1678-4685-gmb-2023-0109
|View full text |Cite
|
Sign up to set email alerts
|

DOF gene family expansion and diversification

Edgar Luis Waschburger,
João Pedro Carmo Filgueiras,
Andreia Carina Turchetto-Zolet

Abstract: DOF (DNA binding with one finger) proteins are part of a plant-specific transcription factor (TF) gene family widely involved in plant development and stress responses. Many studies have uncovered their structural and functional characteristics in recent years, leading to a rising number of genome-wide identification study approaches, unveiling the DOF family expansion in angiosperm species. Nonetheless, these studies primarily concentrate on particular taxonomic groups. Identifying DOF TFs within less-represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Based on earlier research, the structure and number of gene families are not only related to the genome of a species, but also to the evolutionary process of a plant ( Lohani et al., 2021 ; Waschburger et al., 2024 ). The research revealed 41 DOF genes in P. simonii , but the count of DOF genes varied across different species.…”
Section: Discussionmentioning
confidence: 99%
“…Based on earlier research, the structure and number of gene families are not only related to the genome of a species, but also to the evolutionary process of a plant ( Lohani et al., 2021 ; Waschburger et al., 2024 ). The research revealed 41 DOF genes in P. simonii , but the count of DOF genes varied across different species.…”
Section: Discussionmentioning
confidence: 99%